One-step preparation of nanosized Ag-PdCo-powder and its alloy formation at low temperature - Khanna, P. K.; Singh, N.; Kulkarni, D.; Marimuthu, R.; Charan, Shobhit; Patil, K. R.; Jain, G. H. (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2007)
Nano-sized silver-palladium co-powder has been synthesized from silver nitrate-palladium chloride by wet chemical method. The present experimental conditions are applied for the first time for Ag-Pd co-powders wherein sodium formaldehyde sulfoxylate (SFS) has been used as an external reducing agent to simultaneously reduce respective metal salts. SFS reduces the metal salts at room temperature thus prevents formation of bigger particles of the respective metals in co-powder. Powder X-ray diffraction measurements ( XRD) and Transmission electron microscopy ( TEM) suggest the formation of nano-sized Ag-Pd co-powder with particle diameter in the range of about 25 nm. SEM shows that the powder morphology changes with temperature. Heat treatment of 90: 10 (Ag:Pd) composition showed shift in XRD peaks indicating alloy formation of Ag/Pd at lower temperature. Thick-films generated by use of the co-powder resulted in Ag/Pd alloy at about 500 degrees C as confirmed by the XRD. Thermal analysis showed that Ag/Pd co-powders initially gain the weight due to oxidation followed by the weight loss.
Keywords: alloy; Chemical synthesis; nano-powder; noble metal; Transition Metal

Novel solar light driven photocatalyst, zinc indium vanadate for photodegradation of aqueous phenol - Mahapure, Sonali A.; Rane, Vilas H.; Ambekar, Jalindar D.; Nikam, Latesh K.; Marimuthu, R.; Kulkarni, Milind V.; Kale, Bharat B. (Materials Research Bulletin, 2011)
In the present investigation, we have demonstrated the synthesis of novel photocatalyst, zinc indium vanadate (ZIV) by solid solid state route using respective oxides of zinc, indium and vanadium. This novel photocatalyst was characterized using XRD, FESEM, UV-DRS and FTIR in order to investigate its structural, morphological and optical properties. XRD clearly shows the formation of phase pure ZIV of triclinic crystal structure with good crystallinity. FESEM micrographs showed the clustered morphology having particle size between 0.5 and 1 mu m. Since, optical study showed the band gap around 2.8 eV, i.e. in visible region, we have performed the photocatalytic activity of phenol degradation under visible light irradiation. The photodecomposition of phenol by ZIV is studied for the first time and an excellent photocatalytic activity was obtained using this novel photocatalyst. Considering the band gap of zinc indium vanadate in visible region, it will also be the potential candidate for water splitting. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Chemical synthesis; Oxides; X-ray diffraction